Sustainable hydraulic barrier design technologies for effective infrastructure engineering - Wijeyesekera, Devapriya Chitral; Wooi, Eric Kee Loh; Lim, Alvin John Meng Siang (EDP Sciences, 2017)
Migration of liquids lead to embarrassing post construction scenarios such as that of leaks from roofs, potable water leaking from water tanks/ reservoirs, rising damp in walls with groundwater seeping into basement structures, leakage of water from ornamental lakes and ponds or leachate leakage into the environment from MSW landfill sites. Such failures demand immediate and expensive maintenance. A stringent control on structural and waterproof stability is deemed necessary for long term service life of structures and in particular underground and near surface structures. On a micro scale and over a longer time scale, the phenomenon of rising dampness occurs in older buildings with the groundwater rising up through walls, floors and masonry via capillary action. Even slower rates of contaminant fluid migration occur through landfill base liners. In this paper a variety of hydraulic barrier technologies is critically discussed against a backdrop of relevant case studies. The choice of an appropriate hydraulic barrier technology for a given scenario will depend also on the sustainability, financial affordability and subjective aesthetics.